Sickle cell disease in Germany: Results from a national registry. Issue 4 (22nd December 2019) - Kunz, Joachim B.; Lobitz, Stephan; Grosse, Regine; Oevermann, Lena; Hakimeh, Dani; Jarisch, Andrea; Cario, Holger; Beier, Rita; Schenk, Daniela; Schneider, Dominik; Groß‐Wieltsch, Ute; Prokop, Aram; et al.
Abstract: Background: Limited data on the prevalence and medical care of sickle cell disease (SCD) in Germany are available. Here, we make use of a patient registry to characterize the burden of disease and the treatment modalities for patients with SCD in Germany. Procedure: A nationwide German registry for patients with SCD documents basic data on diagnosis and patient history retrospectively at the time of registration. A prospective annual documentation provides more details on complications and treatment of SCD. For the current analyses, data of 439 patients were available. Results: Most patients had homozygous SCD (HbSS 75.1%, HbS/β‐thalassemia 13.2%, and HbSC 11.3%). The median age at diagnosis was 1.9 years (interquartile range, 0.6‐4.4 years), most patients were diagnosed when characteristic symptoms occurred. Sepsis and stroke had affected 3.2% and 4.2% of patients, respectively. During the first year of observation, 48.3% of patients were admitted to a hospital and 10.1% required intensive care. Prophylactic penicillin was prescribed to 95.6% of patients with homozygous SCD or HbS/β thalassemia below the age of six and hydroxycarbamide to 90.4% of patients above the age of two years. At least one annual transcranial Doppler ultrasound was documented for 74.8% of patients between 2 and 18 years. Conclusion: With an estimated number of at least 2000, the prevalence of SCD in Germany remains low. Prospectively, we expect that the quality of care for children with SCD will be further improved by an earlier diagnosis after the anticipated introduction of a newborn screening program for SCD.